PHRASEOLOGY AS A LINGUISTIC BRANCH - Rasulova Shahnoza Abduvasi qizi (Sciental Journals Publishing, 2025)
This article examines phraseology as a significant and independent branch of modern linguistics. Phraseological units – including idioms, proverbs, sayings, and other fixed expressions – are analyzed as important elements that reflect the national and cultural characteristics of a language. The paper explores the structural, semantic, and functional features of phraseological units and their role in both spoken and written discourse. Additionally, it highlights the interconnection of phraseology with other linguistic disciplines such as semantics, stylistics, and lexicology. The challenges of translating phraseological units, their role in conveying the mentality of a nation, and their importance in intercultural communication are also discussed.
Keywords: Phraseology, phraseological units, idioms, semantics, structure, lexicology, stylistics, translation, intercultural communication, linguistics, spoken and written discourse, national mentality, fixed expressions.